PENGARUH PELAYANAN TERHADAP KEPUASAN PELANGGAN TOKO DHINI - Royan Rosyadi (EKSYDA: Jurnal Studi Ekonomi Syariah, 2020)
In the business world, service is a thing that greatly affects success, with service, consumers will get many benefits. To get the maximum profit, customer satisfaction really needs to be considered carefully given the very competitive business conditions. Because human needs tend to be the same while the providers of needs are not only one, this triggers competition. So the main priority that must be considered in assessing the importance of company service quality is the extent to which the service can create the maximum possible level of satisfaction for consumers. This study uses a qualitative approach. With data collection techniques using interviews, observation, and documentation. On the indicators of good waiters' attitude, it is shown that they do not force customers to buy unwanted goods, then the attention indicator is asking for news and not speaking in a loud tone, the indicators of good appearance are seen in a very clean and comfortable shop and the indicators of responsibility are seen from good quality goods and never make customers wait. The data from this observation and interview research aims to provide a firm statement on store services, the results of documentation show that good service and facilities make customers feel satisfied, with results that are considered sufficient based on the collection of observation data, interviews, and documentation showing that service has an effect on customer satisfaction.